Dynamics of The Formation of The Association of Owners And Residents of Apartment Units In The Management of Commercial Flats (Apartments) - Yuniyanti, Salma Suroyya; Abidin, Muhammad Ilman (Fakultas Hukum, Universitas Islam Bandung, 2024)
The purpose of the state administration is to realize a just and prosperous community life by meeting the needs of everyone entitled to a habitable residence as stipulated in Article 28h of the 1945 Constitution. To meet the housing needs, the government issued Law No. 20 of 2011 on flats. The basic philosophy of Law No. 20 of 2011 on flats as the executor of Agrarian Basic Law for the greatest prosperity of the people. However, in practice, it still raises legal issues regarding the management of commercial flats. The purpose of the study is to assess the workings of the application of law in the rules of management of flats in Indonesia. The results of the analysis obtained the difference in the meaning of Article 59 paragraph (2) with an explanation of Article 59 paragraph (1) of Law No. 20 of 2011 regarding the meaning of the unclear and the existence of multiple interpretations. This is due to a dispute between the developers and the owners and residents because of the legal provisions referred to in the management of commercial flats. Development actors are always stalling to facilitate the formation of the Association of Owners and residents of apartment units. Thus, causing legal uncertainty for residents and apartment unit owners in the management of flats.